The Influence of Halal Certification and Halal Awareness on Purchasing Decisions - Purnomo, Irfan Agung; Pratikto, Heri; Suharsono, Naswan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Economic developments have required the food and beverage industry to further develop by bringing out the latest product innovations. This challenge also answers questions from consumers regarding food not just as a basic necessity but as a complement to human lifestyle. As a country with a Muslim majority, the state is an important part of being a facilitator to guarantee the halalness of products in circulation. The method in this research uses quantitative descriptive analysis methods. With the consumer population in Blitar district. This study was conducted using a